Ivermectin-induced gene expression changes in adult Parascaris univalens and Caenorhabditis elegans: a comparative approach to study anthelminthic metabolism and resistance in vitro - Faruk Dube; Andrea Hinas; Shweta Roy; Frida Martin; Magnus Åbrink; Staffan Svärd; Eva Tydén (Parasites & Vectors, 2022)
Abstract Background The nematode Parascaris univalens is one of the most prevalent parasitic pathogens infecting horses but anthelmintic resistance undermines treatment approaches. The molecular mechanisms underlying drug activity and resistance remain poorly understood in this parasite since experimental in vitro models are lacking. The aim of this study was to evaluate the use of Caenorhabditis elegans as a model for P. univalens drug metabolism/resistance studies by a comparative gene expression approach after in vitro exposure to the anthelmintic drug ivermectin (IVM). Methods Twelve adult P. univalens worms in groups of three were exposed to ivermectin (IVM, 10–13 M, 10–11 M, 10–9 M) or left unexposed for 24 h at 37 °C, and total RNA, extracted from the anterior end of the worms, was sequenced using Illumina NovaSeq. Differentially expressed genes (DEGs) involved in metabolism, transportation, or gene expression with annotated Caernorhabditis elegans orthologues were identified as candidate genes to be involved in IVM metabolism/resistance. Similarly, groups of 300 adult C. elegans worms were exposed to IVM (10–9 M, 10–8 M and 10–7 M) or left unexposed for 4 h at 20 °C. Quantitative RT-PCR of RNA extracted from the C. elegans worm pools was used to compare against the expression of selected P. univalens candidate genes after drug treatment. Results After IVM exposure, 1085 DEGs were found in adult P. univalens worms but the relative gene expression changes were small and large variabilities were found between different worms. Fifteen of the DEGs were chosen for further characterization in C. elegans after comparative bioinformatics analyses. Candidate genes, including the putative drug target lgc-37, responded to IVM in P. univalens, but marginal to no responses were observed in C. elegans despite dose-dependent behavioral effects observed in C. elegans after IVM exposure. Thus, the overlap in IVM-induced gene expression in this small set of genes was minor in adult worms of the two nematode species. Conclusion This is the first time to our knowledge that a comparative gene expression approach has evaluated C. elegans as a model to understand IVM metabolism/resistance in P. univalens. Genes in P. univalens adults that responded to IVM treatment were identified. However, identifying conserved genes in P. univalens and C. elegans involved in IVM metabolism/resistance by comparing gene expression of candidate genes proved challenging. The approach appears promising but was limited by the number of genes studied (n = 15). Future studies comparing a larger number of genes between the two species may result in identification of additional candidate genes involved in drug metabolism and/or resistance. Graphical Abstract